Engineering crystals that facilitate the acyl-transfer reaction: insight from a comparison of the crystal structures of myo-inositol-1,3,5-orthoformate-derived benzoates and carbonates - Tamboli, Majid I.; Krishanaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (ACTA Crystallographica Section C-Structural Chemistry, 2016)
Minor variations in the molecular structure of constituent molecules of reactive crystals often yield crystals with significantly different properties due to altered modes of molecular association in the solid state. Hence, these studies could provide a better understanding of the complex chemical processes occurring in the crystalline state. However, reactions that proceed efficiently in molecular crystals are only a small fraction of the reactions that are known to proceed (with comparable efficiency) in the solution state. Hence, for consistent progress in this area of research, investigation of newer reactive molecular crystals which support different kinds of reactions and their related systems is essential. The crystal structures and acyl-transfer reactivity of a myo-inositol-1,3,5-orthoformate-derived dibenzoate and its carbonate (4-O-benzoyl-2-O-phenoxycarbonyl-myo-inositol 1,3,5-orthoformate, C21H18O9) and thiocarbonate (4-O-benzoyl-2-O-phenoxythiocarbonyl-myo-inositol 1,3,5-orthoformate, C21H18O8S) analogs are compared with the aim of understanding the relationship between crystal structure and acyl-transfer reactivity. Insertion of an O atom in the acyl (or thioacyl) group of an ester gives the corresponding carbonate (or thiocarbonate). This seemingly minor change in molecular structure results in a considerable change in the packing of the molecules in the crystals of myoinositol-1,3,5-orthoformate-derived benzoates and the corresponding carbonates. These differences result in a lack of intermolecular acyl-transfer reactivity in crystals of myo-inositol-1,3,5-orthoformate-derived carbonates. Hence, this study illustrates the sensitivity of the relative orientation of molecules, their packing and ensuing changes in the reactivity of resulting crystals to minor changes in molecular structure.